Safety evaluation of the food enzyme rennet containing chymosin and pepsin A from the abomasum of calves and cows - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme containing chymosin (EC 3.4.23.4) and pepsin A (EC 3.4.23.1) is prepared from the abomasum of calves and cows (Bos taurus) by Chr. Hansen. The food enzyme is intended to be used in milk processing for cheese production and in milk processing for the production of fermented milk products. As no concerns arise from the animal source of the food enzyme, from its manufacture, and based on the history of safe use and consumption, the Panel considered that toxicological data were unnecessary and an estimation of dietary exposure was not required. A search for the similarity of the amino acid sequences of the two proteins (chymosin and pepsin A) to those of known allergens was made and one match with pig pepsin, a respiratory allergen, was found. The Panel considered that, under the intended conditions of use, the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.